L'organizzazione delle biblioteche - Ranganathan, Shiyali Ramamrita (Biblioteche & bibliotecari / Libraries & librarians, 2023)
In 1947 in India a large feeling of excitement spreads out the whole country for a new nation to be built, starting from its cultural pillars: schools and libraries. This is the background for the publishing of Ranganathan's The Organization of libraries. With this book, Ranganathan aims «to relate library organization to education» and to provide «a description of library technique in brief». The threefold structure of the work clearly shows its objective of being a means of promotion for a new national library system in India, and the role that should be played by school libraries in this process. Part 1 is devoted to Library and Education, Part 2 to Library practice, and Part 3 to The national library system.